The Role of testosterone treatment in patients with metabolic disorders. Issue 9 (2nd September 2021) - Corona, Giovanni; Rastrelli, Giulia; Vignozzi, Linda; Barbonetti, Arcangelo; Sforza, Alessandra; Mannucci, Edoardo; Maggi, Mario
ABSTRACT: Introduction: The specific role of testosterone [T] replacement therapy [TRT] on glycometabolic profile and body composition, particularly in patients with metabolic syndrome [MetS] and/or type 2 diabetes mellitus [T2DM], is still the object of an intense debate. Areas covered: To discuss available evidence on the association between T and metabolic diseases and on the possible effect of T administration on metabolic disorder-associated hypogonadism. Both preclinical and clinical data have been considered. In addition, a meta-analysis of the available placebo and non-placebo-controlled randomized clinical trials [RCTs] investigating the effects of TRT in T2DM or MetS in several outcomes has been also performed. Expert opinion: Data derived from preclinical and clinical studies suggest that T administration, by reducing fat mass, can improve body composition and ameliorate some aspects of glucose metabolism. The effects of TRT on sexual function in patients with established metabolic derangements are inconsistent, whereas better results were observed in preclinical conditions or in patients with newly diagnosed T2DM.